Value of Risk in the Outdoor Educational Experience - Milena Masseretti; Michela Schenetti (University of Bologna, 2024)
Starting from a phenomenological reflection, the contribution deals with the theme of risk as an aspect inseparable from human nature, as uncertainty and precariousness are constitutive parts of the existence itself. Reflecting on the concept of beneficial risk and the role that education, adults and the whole society should have with regard to risk, it is highlighted how, on the contrary, overprotection generates negative effects in the long run. This conviction is supported by researches involving overprotective parents' children, or the implications of zero risk in playgrounds. The natural task of education at different levels, micro- meso- eso- and macro-system, consists in equipping boys and girls in order to become acquainted with risk, providing children with appropriate strengths and means, making their lives not as safe as possible, but as safe as necessary.